Epidemiological Characteristics and Influencing Factors of Myopia Among Primary School Students in Southern China: A Longitudinal Study - Jingfeng Mu; Dan Zeng; Jingjie Fan; Meizhou Liu; Mingjie Jiang; Xinyi Shuai; Jiantao Wang; Shaochong Zhang (Frontiers Media S.A., 2023)
Objectives: To study the epidemiological characteristics and influencing factors of myopia to provide a scientific basis for the prevention and control of myopia.Methods: 7,597 students studying in grades 1-3 were followed up. Eye examinations and questionnaire surveys were conducted annually from 2019 to 2021. The influencing factors of myopia were analyzed by logistic regression model.Results: The prevalence of myopia among students in grades 1-3 in 2019 was 23.4%, which increased to 41.9% and 51.9% after the 1-and 2-year follow-up, respectively. The incidence of myopia and change in the spherical equivalent refraction (SER) were higher in 2020 than in 2021. The 2-year cumulative incidences of myopia were 2.5%, 10.1%, 15.5%, 36.3%, and 54.1% in students with a baseline SER >+1.50D, +1.00D to +1.50D, +0.50D to +1.00D, 0.00D to +0.50D, and -0.50D to 0.00D, respectively. Outdoor activities, sex, age, baseline SER, parental myopia, sleep time, and digital device exposure were associated with myopia.Conclusion: The prevalence of myopia demonstrated a rapid increase; thus, healthy habits and outdoor activities should be promoted for the prevention and control of myopia.